Weighted Composition Operators between Weighted Bergman Spaces and Weighted Banach Spaces of Holomorphic Functions - Wolf, Elke (Revista Matemática Complutense, 2008)
We characterize boundedness and compactness of weighted composition operators acting between weighted Bergman spaces Aw;p and weighted Banach spaces H1v of holomorphic functions.